Las docentes de Educación Inicial y Parvularia y su rol en la atención de niños y niñas con necesidades educativas especiales. - Villavicencio Aguilar, Carmita Esperanza (2015)
The objective of this work was to determine the relationship between vocational training of teachers and their ability to assist children with sne. It was materialized through the implementation of anonymous surveys teachers dimensions, planner, facilitator and research training and questionnaires to students dimensions, Sensitivity to rights of children, knowledge of diversity sne and curricular adaptations of career early childhood education and early childhood of Technical University of Machala Ecuador, in the period 2013.